2022
DOI: 10.1002/chem.202200078
|View full text |Cite
|
Sign up to set email alerts
|

A Universal DNA Aptamer that Recognizes Spike Proteins of Diverse SARS‐CoV‐2 Variants of Concern

Abstract: We report on a unique DNA aptamer, denoted MSA52, that displays universally high affinity for the spike proteins of wildtype SARS‐CoV‐2 as well as the Alpha, Beta, Gamma, Epsilon, Kappa, Delta and Omicron variants. Using an aptamer pool produced from round 13 of selection against the S1 domain of the wildtype spike protein, we carried out one‐round SELEX experiments using five different trimeric spike proteins from variants, followed by high‐throughput sequencing and sequence alignment analysis of aptamers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…For example, the ranking of MSA52R1 increased from 46 th in the WH pool to 14 th in the CA pool, producing a ranking increase of 69.5 %. [38] The results once again confirmed that the members in this family competed well for the binding of all four variants used for selection. Taken together, the sequencing analysis identified MSA52 as a universal aptamer candidate for the S protein.…”
Section: Selection Of Universal Aptamerssupporting
confidence: 62%
See 4 more Smart Citations
“…For example, the ranking of MSA52R1 increased from 46 th in the WH pool to 14 th in the CA pool, producing a ranking increase of 69.5 %. [38] The results once again confirmed that the members in this family competed well for the binding of all four variants used for selection. Taken together, the sequencing analysis identified MSA52 as a universal aptamer candidate for the S protein.…”
Section: Selection Of Universal Aptamerssupporting
confidence: 62%
“…However, the ranking of MSA52 increased to 24 th , 19 th , 17 th , and 14 th after one‐round selection with the S protein from the UK (UKS), Brazil (BZS), South Africa (SAS), and California (CAS) variants, respectively, but remained largely unchanged (with a ranking of 46 th ) in the pool with the wildtype S protein (WHS). [38] These observations indicate that MSA52 competed favorably for binding all four S protein variants with the top‐ranking sequences established using WHS, pointing to the possibility of this aptamer being the universal aptamer that we were searching for.…”
Section: Selection Of Universal Aptamersmentioning
confidence: 87%
See 3 more Smart Citations